TRANSVERSE IMPEDANCE OF THE SQUID GIANT AXON DURING CURRENT FLOW - Cole, Kenneth S. (The Rockefeller University Press, 1941)
The change in the transverse impedance of the squid giant axon caused by direct current flow has been measured at frequencies from 1 kc. per second to 500 kc. per second. The impedance change is equivalent to an increase of membrane conductance at the cathode to a maximum value approximately the same as that obtained during activity and a decrease at the anode to a minimum not far from zero. There is no evidence of appreciable membrane capacity change in either case. It then follows that the membrane has the electrical characteristics of a rectifier. Interpreting the membrane conductance as a measure of ion permeability, this permeability is increased at the cathode and decreased at the anode.